Utlenianie 4- i 5-pierścieniowych węglowodorów w obecności węgla aktywnego = Oxidation of pahs in presence of activated carbon - Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study was to determine the removal of 4- and 5-rings of PAHs during oxidation process and during oxidation and adsorption simultaneous processes. Technological research was conducted with the use of biologically purified coking wastewater. Oxidation was carried out with dihydrogen peroxide. The adsorption process with activated carbon was carried out.
Keywords: WWA; utlenianie; ditlenek diwodoru; adsorpcja; węgiel aktywny; GC-MS; PAHs; oxidation; dihydrogen peroxide; adsorption; activated carbon